Proposal for a tool for the applicability of VR and BCI in an interdisciplinary study to infer attention in individuals with ADHD - Malaquias, Pedro Igor de Souza; Alvarenga, Victor Ferreira; Coelho, Mateus Nazario; Santanna, Adriene; Christianne, Christianne; Delabrida, Saul (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a persistent pattern of inattention and/or hyperactivity-impulsivity and has behavioral and pharmacological treatments as alternatives. For action in behavioral treatment, there are several alternatives based on psychological techniques. The present study presents the proposal of evaluating the attention rate of an individual with ADHD by using virtual reality equipment, brainwave analysis, and eye movement tracking. The proposal emerges as a way of integrating psychometric methods aligned with current technologies that can offer data to measure parameters that determine attention. The presented method uses virtual reality as a stimulus scenario, controlled by the researchers and professionals involved, and subsequently performs the reading of brainwaves to capture data. The research’s innovation is the integration of technologies that have recently become available for mass use with psychometric methods, especially for people with ADHD, and it explores how health professionals can use data obtained from technological artifacts. The present work is a collaboration of a multidisciplinary team formed by computing and pedagogy researchers and a psychology professional.